Circadian rhythms in exercise performance: Implications for hormonal and muscular adaptation - Teo, W.; Newton, M. J.; McGuigan, M. R. (Journal of Sports Science & Medicine, 2011)
Almost all physiological and biochemical processes within the human body follow a circadian rhythm (CR). In humans, the suprachiasmatic nucleus regulates sleep- wake cycle and other daily biorhythms in line with solar time. Due to such daily physiological fluctuations, several investigations on neuromuscular performance have reported a distinct CR during exercise. Generally, peak performances have been found to occur in the early evening, at approximately the peak of core body temperature. The increase in core body temperature has been found to increase energy metabolism, improve muscle compliance and facilitate actin-myosin crossbridging. In addition, steroidal hormones such as testosterone (T) and cortisol (C) also display a clear CR. The role of T within the body is to maintain anabolism through the process of protein synthesis. By contrast, C plays a catabolic function and is involved in the response of stress. Due to the anabolic and catabolic nature of both T and C, it has been postulated that a causal relationship may exist between the CR of T and C and muscular performance. This review will therefore discuss the effects of CR on physical performance and its implications for training. Furthermore, this review will examine the impact of muscular performance on CR in hormonal responses and whether could variations in T and C be potentially beneficial for muscular adaptation.